A rare cause of maxillary mass: juvenile ossifying fibroma - Şereflican, Murat; Yurttaş, Veysel; Ozan, Fatih; Akkaş, İsmail and Dağlı, Muharrem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Juvenile ossifying fibroma (JOF) is a unique fibro-osseous neoplasm. It has 2 histopathological variants. Psammomatoid juvenile ossifying fibroma (PsJOF) and Trabecular juvenile ossifying fibroma (TrJOF) affecting the jaws of children. Only 20% of the patients are over 15 years of age. JOF is more common in maxilla than mandible. It presents as an asymptomatic progressive, rapid expansion of jaws. It has a recurrence rate of 30-58%. Surgery is the only cure for this kind of lesion and total excision should be the goal of the treatment. We present a case report of 12 year-old female patient with clinical, radiographic and histopathological features of Psammomatoid JOF which clinically admitted to our clinic as maxillary sinus mass.